2004
DOI: 10.1177/0734242x04044970
|View full text |Cite
|
Sign up to set email alerts
|

Sampling Household Waste at Source: Lessons Learnt in Gaborone

Abstract: Municipal solid waste (MSW) quantity and composition analysis is fundamental for the planning of municipal waste management services. The purpose of this paper is to report the results and experiences of sampling household waste at the source of generation in Gaborone, Botswana. The average generation rate, in kg capita(-1) day(-1), and percentages of various components of waste in Gaborone were determined using a statistically designed household sampling survey. The survey covered 47 households with different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
3
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 8 publications
6
33
3
2
Order By: Relevance
“…The ST3's distribution peaked because the coefficient of kurtosis was higher than the coefficient of kurtosis of the normal distribution, which was equal to 3 14), 16), 22) . Previous studies used mean estimates and standard deviation (SD) 16), 23)- 26) to describe the confidence interval of waste generation rate by tolerating the small amount of skewness to have Normal distribution 22) . However, in this study we used geometric mean and standard deviation for statistical estimates of waste generation rate 14) .…”
Section: Results and Discussion (1) Municipal Waste Generation A) Homentioning
confidence: 99%
See 1 more Smart Citation
“…The ST3's distribution peaked because the coefficient of kurtosis was higher than the coefficient of kurtosis of the normal distribution, which was equal to 3 14), 16), 22) . Previous studies used mean estimates and standard deviation (SD) 16), 23)- 26) to describe the confidence interval of waste generation rate by tolerating the small amount of skewness to have Normal distribution 22) . However, in this study we used geometric mean and standard deviation for statistical estimates of waste generation rate 14) .…”
Section: Results and Discussion (1) Municipal Waste Generation A) Homentioning
confidence: 99%
“…For stratified random sampling, population mean of waste generation and composition was unbiasedly estimated by a weighted average of means of strata 15), 16) , described by the following equation:…”
Section: (3) Statistical Analysismentioning
confidence: 99%
“…As the number of household occupant's increases, waste generation has been found to decrease per person, mainly because of economies of scale in the consumption of goods and packaging in developing countries [21]. Nevertheless, "Abu-qdais et al [21] found" a statistically significant but weak negative relationship between waste generation and household size in Abu Dhabi (R 2 = 0.11), while "Bolaane et al [22] found" a similar weak negative relationship in Gabarone, Botswana (R 2 = 0.34). However, "Parizeau et al [18] found" a weak (R 2 = 0.35), but significant (p = 0.000) negative relationship between waste generation and household size.…”
Section: Relationship Of Waste Generation To Household Sizementioning
confidence: 93%
“…Já Bolaane & Ali (2004) apontam uma média de 68%; sendo assim, quando esses resultados são comparados com os do presente estudo, que compreende uma faixa de 40,2 a 68,4%, nota-se que a geração mínima é compatível com a do Banco Mundial, mas a máxima difere deste. Mas, por outro lado, adere-se à média de Bolaane & Ali (2004), o que pode ser explicado em função da quantidade de estudos em países desenvolvidos, em desenvolvimento e subdesenvolvidos utilizados, pois há uma variação de geração de resíduos dependendo da classificação do país. A fração de geração de resíduos orgânicos em todos os grupos de rendas (países desenvolvidos, em desenvolvimento ou subdesenvolvimento) (Tabela 3) corresponde a maior representação; assim, esse resultado adere-se às afirmações de Bolaane & Ali (2004).…”
Section: Materiais E Métodosunclassified
“…Mas, por outro lado, adere-se à média de Bolaane & Ali (2004), o que pode ser explicado em função da quantidade de estudos em países desenvolvidos, em desenvolvimento e subdesenvolvidos utilizados, pois há uma variação de geração de resíduos dependendo da classificação do país. A fração de geração de resíduos orgânicos em todos os grupos de rendas (países desenvolvidos, em desenvolvimento ou subdesenvolvimento) (Tabela 3) corresponde a maior representação; assim, esse resultado adere-se às afirmações de Bolaane & Ali (2004). …”
Section: Materiais E Métodosunclassified